Uncovering the Phytochemical Profile, Antioxidant Potency, Anti-Inflammatory Effects, and Thrombolytic Activity in Dendrobium lindleyi Steud. - Minhajur Rahman; Roxy Begum; Abu Taleb Surag; Md. Shakhuat Hossain Tusher; Mohammed Kamrul Huda (Scientifica)
Background. Dendrobium genus has been used in traditional medicine to treat various illnesses. The study aims at examining the phytochemical, antioxidant, anti-inflammatory, and thrombolytic properties of the leaf, stem, and root of Dendrobium lindleyi Steud, and the relationship between phytochemicals and bioactivities is determined. Results. The qualitative screening found a variety of bioactive compounds, including alkaloids, coumarins, cardiac glycosides, glycosides, flavonoids, proteins, phenols, quinines, resins, steroids, saponins, tannins, and terpenoids, in varying amounts. The quantitative screening showed the highest concentration of alkaloids in the leaves (172.15 ± 1.22 mg/g), phenols in the root (203.55 ± 0.75 mg/g), flavonoids in the root (24.35 ± 0.42 mg/g), tannins in the leaves (105.06 ± 0.55 mg/g), and proteins in the root (194.12 ± 0.65 µg/ml). The root extract showed the highest antioxidant activity (IC50 = 58.24 µg/mL), the stem extract had the most increased thrombolytic activity (IC50 = 242.74 µg/mL), and the leaf extract had the most potent anti-inflammatory activity (IC50 = 61.79 µg/mL). Statistical analysis revealed a significant positive relationship (p=0.05) between alkaloids (r = 0.96) and tannins (r = 0.9) with antioxidant, anti-inflammatory, and thrombolytic properties. Conclusion. The bioactivities of D. lindleyi, including antioxidant (root), thrombolytic (stem), and anti-inflammatory (leaf) activities, are linked to the phytochemicals detected in the screening.